Peran keluarga dan teman sebaya dalam membentuk identitas sosial: social identity - Isna Mazroah; Mamun Hanif (Universitas Islam Raden Rahmat Malang, 2025)
This study aims to explore the role of family and peers in shaping individuals' social identity, particularly in the context of education. Using a qualitative approach based on a literature review, this research analyzes relevant literature on the roles of family and peers as primary agents of socialization. The findings indicate that families provide foundational values, norms, and cultures that serve as the initial reference for forming social identity, while peers act as a social environment that supports the exploration and reinforcement of individual identity. These findings integrate perspectives from educational sociology theories, including functionalism, symbolic interactionism, and sociocultural theories, to provide a comprehensive understanding of how interactions between family and peers influence the development of social identity. This study is expected to serve as a reference for the development of inclusive and socially and culturally sensitive educational policies.